Efektivitas Penggunaan Rekam Medis Elektronik Terhadap Peningkatan Kualitas Pelayanan Pasien di Rumah Sakit - Fita Rusdian Ikawati (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to explore the benefits and challenges of EMR implementation and its implications for medical practices and healthcare services in Indonesia. The research design utilizes a Literature Review. Sources used in searching for literature in this research include Google Scholar, ScienceDirect, DOAJ, and Scopus. Furthermore, in conducting literature selection, the researcher uses the PRISMA method. This study identifies the benefits of EMR in accelerating patient information access, enhancing coordination among medical teams, and reducing the risk of errors in medical data recording. However, challenges such as data security and staff training are also faced in EMR implementation. In conclusion, the implementation of EMR in Indonesian hospitals promises significant benefits in improving the efficiency, accuracy, and quality of healthcare services, although it still faces some obstacles that need to be addressed.